Family dynamics and support network of family caregivers of people with progressive cancer - Larissa Carvalho Saletti; Mariana Lectícia Beraldi; Ana Lucia de Moraes Horta (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To analyze family dynamics, the support network of family caregivers of individuals with progressive cancer, and their needs for comprehensive care. Method: Qualitative, descriptive study developed based on the Calgary Family Assessment Model framework. It was conducted from September 2022 to April 2023, through participant observation at a public health institution in São Paulo and interviews with six family caregivers. The analysis was performed using Genogram and Ecomap, following the Calgary Model, with the support of software for data organization. Results: The data were categorized into structural, developmental, and functional family assessments. They revealed the strengthening of family relationships with strong bonds, an increased level of burden on the caregiver as cancer progressed, neglect of self-care, and financial difficulties. Due to the burden, caregivers struggled to outline the composition of their support network, but the employed model enabled the identification of its elements, with faith being mentioned by all. Conclusion: The diagnosis and progression of cancer led to changes in family structure, development, and functionality which need to be individually assessed to improve care planning. This involves mobilizing elements and services according to the reality of families.